Seed Priming Alters the Production and Detoxification of Reactive Oxygen Intermediates in Rice Seedlings Grown under Sub-optimal Temperature and Nutrient Supply - Hussain, Saddam; Khan, Fahad; Cao, Weidong; Wu, Lishu; Geng, Mingjian (Frontiers in Plant Science, 2016)
The production and detoxification of reactive oxygen intermediates (ROIs) play an important role in the plant response to nutrient and environmental stresses. The present study demonstrated the behavior of growth, ROIs-production and their detoxification in primed and non-primed rice seedlings under chilling stress (18˚C) and nitrogen-(N), phosphorus-(P), or potassium-(K) deprivation. The results revealed that chilling stress as well as deprivation of any mineral nutrient severely hampered the seedling growth of rice, however, seed priming treatments (particularly selenium- or salicylic acid-priming), were effective in enhancing the rice growth under stress conditions. The N-deprivation caused the maximum reduction in shoot growth, while the root growth was only decreased by P- or K-deprivation. Although, N-deprivation enhanced the root length of rice, the root fresh weight was unaffected. Rate of lipid peroxidation as well as the production of ROIs, was generally increased under stress conditions; the K-deprived seedlings recorded significantly lower production of ROIs than N- or P-deprived seedlings. The responses of enzymatic and non-enzymatic antioxidants in rice seedlings to chilling stress were variable with nutrient management regime. All the seed priming were found to trigger or at least maintain the antioxidant defense system of rice seedlings. Notably, the levels of ROIs were significantly reduced by seed priming treatments, which were concomitant with the activities of ROIs-producing enzymes (monoamine oxidase and xanthine oxidase), under all studied conditions. Based on these findings, we put forward the hypothesis that along with role of ROIs-scavenging enzymes, the greater tolerance of primed rice seedlings can also be due to the reduced activity of ROIs-producing enzymes.